Assessment of mothers awareness on acute malnutrition - Karikari, Evelyn; Sokolov, Nikita; Mikerova, Maria; Asiedu-Ayeh , Benjamin; Karikari, Modesta; Ameyaw , David; Kawuo , Sampson; Nikolic Turnic, Tamara (Medicinski časopis, 2025)
Background and Aim: According to the American Society of Parenteral and Enteral Nutrition (ASPEN), pediatric malnutrition is defined as “an imbalance between nutrient requirement and intake, resulting in cumulative deficits of energy, protein, or micronutrients that may negatively affect growth, development, and other relevant outcomes.” The purpose of this study was to assess guardians’ awareness of Acute Malnutrition and its management in Ghana.Method: This qualitative research employed the grounded theory study design. 15 participants were interviewed from the SMALCHILD (Save the Malnourished Child) clinic of Holystic Nutrition Organization, Ghana. Microsoft Office Excel was used for analysing data.Results: In this current study, guardians shared their ideas on malnutrition and their previous knowledge of it before seeking for clinical services and four themes were generated: Signs and symptoms of Acute Malnutrition manifested reported by participants as manifested in their children, Misconceptions that participants had about Acute Malnutrition, Initial response by participants to treat Acute Malnutrition and How participants found out about clinical management of Acute Malnutrition.Conclusion: From this research, we observed that participants were able to identify some of the initial signs and symptoms for Acute malnutrition but had some misconceptions. Most thought that the condition was Asraam (which meant that a witch is a cause of that condition), and sought help from Asraam doctors with the use of herbal medications. This alone shows how important it is to educate guardians on Acute Malnutrition to prevent further complication of their children.
Keywords: Awareness, Malnutrition, Acute Malnutrition, Guardians